Estudio de prefactibilidad para la instalación de una planta procesadora de colchonetas de caucho reciclado - Martel Orihuela, Luciana Francesca (2022)
The pre-feasibility study presented below arises due to the lack of tire recycling projects in the country; therefore, it aims to determine the technical, economic, financial and market feasibility of installing a plant to produce recycled rubber mats. These will target people in Metropolitan Lima who belong to NSE A and B between the ages of 13 and 55. First, a market study was carried out with the application of 385 surveys which reflected that there is an unsatisfied market that would be willing to purchase eco-friendly sports mats. This market translates into a projected demand for 2027 – end of the project's life horizon – of 12,929 Cauchonetas. Second, it was determined that the optimal location of the plant will be in the district of San Juan de Lurigancho in the province of Lima, Lima - Peru, whose size will be delimited by the previously mentioned market demand. Likewise, it will have an annual processing capacity of 14,255 mats and a break-even point of 6,558 rubber mats per year. Third, after calculating the costs and expenses required for the start-up of the project, a total investment amount of S/ 1,085,933 is estimated, financed 60% by own capital and 40% with a bank loan. In addition, it is confirmed that the project is economically and financially viable by having a positive Economic and Financial Net Present Value of S/ S/ 622,947 and S/1,030,590 respectively; as well as an Internal Rate of Economic and Financial Return of 28.42% and 37.32%, both being higher than the opportunity cost (15.64%) and, therefore, profitable.